Tangent spaces of the Teichmüller space of the torus with Thurston’s weak metric - Miyachi, Hideki; Ohshika, Ken’ichi; Papadopoulos, Athanase (Annales Fennici Mathematici, 2022)
In this paper, we show that the analogue of Thurston’s asymmetric metric on the Teichmüller space of flat structures on the torus is weak Finsler and we give a geometric description of its unit circle at each point in the tangent space to Teichmüller space. We then introduce a family of weak Finsler metrics which interpolate between Thurston’s asymmetric metric and the Teichmüller metric of the torus (which coincides with the hyperbolic metric). We describe the unit tangent circles of the metrics in this family.